Temporal Profile of Soluble TLR4 and its Association with Intracerebral Haemorrhage Expansion - Maria Lucas-Parra; Carme Gubern-Mérida; Sofia Dávila; Tomàs Xuclà-Ferrarons; Joan Martínez; Saima Bashir; Alan Murillo; Víctor Vera-Monge; Juan Álvarez-Cienfuegos; Laia Carballo-Perich; Elisabet Ortiz; Isabel Vielba-Gomez; et al. (Translational Stroke Research, 2026)
Inflammation contributes to haematoma expansion (HE) and poor prognosis in spontaneous intracerebral haemorrhage (ICH). This study aimed to characterise the temporal profile of soluble Toll-like receptor 4 (sTLR4) during the hyperacute and acute phases of ICH and to evaluate its association with HE. Serum sTLR4 levels were measured at admission, 24 and 72 h from 99 patients with primary hemispheric ICH within 12 h of symptom onset, and at baseline from 39 non-stroke controls using enzyme-linked immunosorbent assay (ELISA). Longitudinal sTLR4 fluctuations were evaluated through linear mixed-effects models. Independent HE prognosticators were identified using multivariable logistic regression, and model performance was assessed via the area under the receiver operating characteristic curve (AUC-ROC). ICH patients exhibited significantly higher baseline sTLR4 levels than controls, which declined over time and were not associated with clinical variables. Notably, patients with HE demonstrated higher admission sTLR4 levels than those without HE (2.50 [95% CI: 1.84–3.16] vs. 1.62 [95% CI: 1.22–2.02] ng/mL, p = 0.027). Furthermore, while the non-HE group showed a rapid decrease within the first 24 h, the HE group maintained elevated levels with a more gradual decline. A multivariable model incorporating baseline ICH volume and sTLR4 levels achieved an AUC of 0.829, with positive and negative predictive values of 70.8% and 90.1%, respectively. These findings suggest that TLR4 may be involved in the pathophysiology of HE, and the combination of baseline ICH volume and sTLR4 levels could serve as a useful tool to stratify patients into low- and high-risk groups for HE.

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Marine life as a source of anti-prostate cancer agents: an updated overview (2003–2023) - Amjad Hussain; Ammara Sohail; Muhammad Sajid Hamid Akash; Sarosh Iqbal; Kanwal Rehman; Muhammad Imran; Shoaib Khan; Muhammad Adnan Ayub; Daijie Wang; Dildar Ahmed; Mohammed Hadi Ali Al-Jumaili; Maria Bashir; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Enhancing maize (Zea mays L.) tolerance to water stress using kaolin and potassium silicate as protective agents - Maria Iqbal; Rohina Bashir; Iqbal Hussain; Saqib Mahmood (Cereal Research Communications, 2025)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

Investigating the effects of a single ASPM variant (c.8508_8509) on brain architecture among siblings in a consanguineous Pakistani family - Komal Aslam; Aysha Saeed; Iffat Jamil; Hafiza Iqra Saeed; Ramisha Khan; Samina Hassan; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; Rasheeda Bashir; Muhammad Sajid Hussain; Shahid Mahmood Baig; et al. (Molecular Biology Reports, 2024)

Nutritional and health promoting perspectives of Monostroma spp. (Chlorophyta): A systematic review - Sana Mansoor; Khawaja Muhammad Imran Bashir; Md. Mohibbullah; Maria Dyah Nur Meinita; Mohammed Nurul Absar Khan; Jae-Hak Sohn; Jae-Suk Choi (Journal of Applied Phycology, 2024)

Weathering and accumulation of trace elements in the soils of the Porali Plain, Balochistan: repercussions in agriculture - Maria Kaleem; Erum Bashir; Shahid Naseem; Tahir Rafique; Bushra Shahab (Acta Geochimica, 2024)